Public Engagement in the Design of Urban Blue‐Green Infrastructure: Contrasting Approaches and Project Outcomes in Ōtautahi Christchurch - Tyler McNabb; David Conradson; Edward Challies; Frances J. Charters; Rita Dionisio (New Zealand Geographer, 2026)
ABSTRACT Although blue‐green infrastructure (BGI) is increasingly used to mitigate the challenges that climate change poses for cities, public involvement in its design is uneven. Here we examine three BGI projects in Ōtautahi Christchurch, Aotearoa New Zealand, documenting how local communities and mana whenua were engaged in their design and the impact on project outcomes. Across the projects, we observed both narrowly consultative and more collaborative forms of public engagement. Collaborative approaches were found to deliver socio‐cultural and ecological benefits beyond those usually associated with flood risk reduction infrastructure. We conclude by outlining how collaborative design approaches can enhance BGI benefits.